2012
DOI: 10.4314/njp.v40i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid fever in children: Clinical presentation and risk factors

Abstract: Objective: The diagnosis of typhoid fever based on widal test is on the rise despite its set back. We prospectively reviewed over one year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
5
4
0
Order By: Relevance
“…This study has shown that suspected typhoid fever cases were common in children aged 5 years and above. This finding agrees with observations made in Nigeria and Pakistan where typhoid fever was more common in children aged 5–9 years [ 49 , 50 ]. A plausible explanation for high prevalence of typhoid fever in older children is the consumption of unsafe locally-made chilled drinks and ice creams at schools since these are school-aged children.…”
Section: Discussionsupporting
confidence: 93%
“…This study has shown that suspected typhoid fever cases were common in children aged 5 years and above. This finding agrees with observations made in Nigeria and Pakistan where typhoid fever was more common in children aged 5–9 years [ 49 , 50 ]. A plausible explanation for high prevalence of typhoid fever in older children is the consumption of unsafe locally-made chilled drinks and ice creams at schools since these are school-aged children.…”
Section: Discussionsupporting
confidence: 93%
“…This study aims to identify various socio-demographic, clinical, and laboratory parameters of typhoid which are significant. Male predominance found in this study is very similar to the finding of Rabasa et al and Ramaswamy et al [ 3 , 5 ]. This may be due to overindulgence in outdoor activities in more boys than girls, therefore exposure to sources of infection.…”
Section: Discussionsupporting
confidence: 92%
“…Socioeconomic status has a very important role to play in hygiene and sanitation and hence tends to affect the incidence of enteric fever. This was reflected in this study as 94% of the affected children belonged to lower or middle socio-economic status, which resembles the findings of a Nigerian study [3].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this prospective study, boys were affected more than girls, with a male-female ratio of 1.4:1, compatible with other studies [ 1 , 43 - 49 ]. Rabasa AI et al found male-female ratio of 3:2 in their study [ 50 ]. In multiple studies, EF was found considerably higher in females than males [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 92%